L_p (D) Approximation by Modified Complex Szasz- Mirakjan Operator - Lafta, Mohammed Hadi; Bhaya, Eman Samir (Iraqi Journal of Science, 2024)
Many operators are introduced for the approximation of real functions, but little for the approximation of complex functions. These studies are for analytic functions. In this article, we define a new type of Szasz-Mirakjan operator. Then we estimate the degree of approximation using this modified complex Szasz-Mirakjan operators to integrable functions on compact disks along with a quantitative estimation. Using quantitative methods, we also obtain an upper estimate in the simultaneous approximation by and exact degrees of approximation estimation for these operators’ Stancu-type generalization.